Formulasi Sabun Cair Pencuci Tangan Kombinasi Minyak Sereh (Cymbopogon Nardus L.) Dan Minyak Kayu Manis (Cinnamomum Burmanni Ness Ex Bi.) - Umi Nafisah; Ester Dwi Antari; Puput Albetia (Universitas Duta Bangsa Surakarta, 2021)
The condition of the people in the midst of an epidemic of diseases caused by a virus that is sweeping the world has made us aware of the importance of cleanliness. One way to prevent transmission of viruses and bacteria is to wash our hands frequently with soap. Natural ingredients that can be developed into soap dosage forms because they have antibacterial activity are lemongrass and cinnamon. This research was conducted to determine the formulation and evaluation of liquid hand soap with a combination of lemongrass and cinnamon essential oil. This research was conducted experimentally, to examine liquid soap with various concentrations of lemongrass and cinnamon oil in formula I 0.25%: 0.25%, formula II 0.5%: 0.25%, formula III 0.25%: 0.5%, and the IV formula 0.5%: 0.5%. The results of the organoleptic examination showed the distinctive smell of lemongrass, in the form of thick liquid, lemon yellow in color, while formula I was pale yellow. The four formulas do not yet meet good pH parameters for hand washing soap. The results of the foam height test in formulas I, II, and III were 9 cm and in formula IV was 9.5 cm. The irritation test showed that the four volunteers had no irritation reactions. The results of the hedonic test show that the respondents gave an average rating response between like to very fond of liquid hand washing soap.